The role of PHET-based virtual laboratories on primary student motivation and conceptual understanding in the Energy Transformation concepts - Sopari; Kurnia Jayadinata, Asep; Ismail, Ali (Research in Physics Education, 2024)
This research was conducted based on the importance of motivation and understanding of concepts at the elementary school level. Learning with a PhET-based virtual laboratory is an innovative approach in science education that can help visualize abstract concepts. A quantitative descriptive method was chosen for this study, with a pre-experimental one-group pretest-posttest design. The sample consisted of fourth-grade students from public primary schools in Indonesia. The instruments used in this study were observation guidelines, questionnaires, and test questions. The results showed that the implementation of PhET-based virtual laboratory learning received an average score of 97.77%, which is considered very good. Motivation after learning with the PhET-based virtual laboratory had an average score of 71%, indicating a good level. Students' conceptual understanding increased after the implementation of PhET-based virtual laboratory learning, with the average pretest score rising from 55.8% to a posttest score of 77.2%.